First Successful Mechanical Splint for Obstructive Sleep Apnea With an Orally Administrable Pharyngeal Stenting Device. (10th August 2018) - Neu, Daniel; Nawara, Grégory; Newell, Johan; Bouchez, David; Mairesse, Olivier
Abstract : We report the case of obstructive sleep apnea in a 19‐year‐old, otherwise healthy male presenting with persistent daytime sleepiness and nonrestorative sleep after velo‐ and uvuloplasty. An individually tailored prototype of an orally inserted pharyngeal stenting device was proposed in the framework of a first clinical feasibility trial. The noninvasive, easily self‐administered device is mounted on a simple inferior dental guard. Baseline total apnea‐hypopnea index (AHI) was 15.5 and 24.4 per hour of rapid eye movement (REM) sleep. With the device, total AHI dropped to 6.7 per hour (56.8% reduction) and 1.4 per hour of REM (94.3% reduction). Recorded sleep efficiency during treatment was excellent at 96.5%. Laryngoscope, 129:1945–1948, 2019